KOMUNIKASI TERAPEUTIK DALAM KONSELING (Studi Deskriptif Kualitatif Tahapan Komunikasi Terapeutik dalam Pemulihan Trauma Korban Kekerasan Terhadap Istri di Rifka Annisa Women’s Crisis Center Yogyakarta) - Etik Anjar Fitriarti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. Violence against wives that occured in Indonesia until now there are still many happened. This resulted in various issues such as the trauma of the victims (clients).This client usually ask for help in social institutions such as Rifka Annisa Women’s Crisis Center as Non Govermental Organization (NGO) that protect, help and the empower women being a victim of violence. Rifka Annisa Women’s Crisis Center give counseling for the client to raise awareness and recovery client’s trauma. Researchers found communication therapeutic happened in counseling because in counseling happened communication that aims to relieve trauma felt by clients. Researchers analyzed use the theory of therapeutic communication and also put it to the theory of 5 stages of grief to know the psychological clients at each stage of the counseling there are denial, anger, offering, sorrow and acceptance. This research uses the method descriptive qualitative. Informants of research are counselors of psychology which were selected purposively sampling. Data is collected through in-depth interviews, observation the field and documentation.This research result indicates therapy communication is done by counselor in counseling that happened 4 steps there are pre interaction, the orientation, the work and the termination. In addition at every step of therapeutic communication was stages of recovery grief.